Penggunaan Bahasa Baku dalam Penulisan Karya Ilmiah - Wulandari, Dinda Riris; Silvia, Cindy; Budiman, Budiman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This essay discusses the factors to consider when using formal language in scientific writing by students. Standard written language is commonly used in scientific studies. In the scientific community, standard language is a requirement. According to the Enhanced Indonesian Spelling (EYD), specific requirements must be fulfilled in writing, including the use of capital letters and italics, assimilation of foreign terms, correct word usage, word truncation, and avoiding word repetition.